The relationship between psychological capital and job performance of employees in Public Service Department (PSD), Putrajaya / Norfatiha Abu - Abu, Norfatiha (Faculty of Business and Management, 2018)
The purpose of this study is to identify the relationship between psychological capital which is self-efficacy, hope, resiliency and optimism toward job performance of employees in Management Service Unit, Public Service Department (PSD), Putrajaya. There are four hypothesis were developed to identify whether there is relationship between self-efficacy, hope, resiliency and hope toward job performance. Respondents are selected from Management Service Unit, Public Service Department (PSD), Putrajaya. The data was conducted by distributing the 200 questionnaires to the employees. Descriptive, correlation and regression analysis was used to analyse data. The results from the Pearson Correlation Analysis showed that all independent variables have correlated with job performance. There is a strong and positive association between self-efficacy, hope and optimism to the job performance. Lastly, there is a moderate and positive association between resiliency and job performance. Furthermore, based on R², it can be seen that the self-efficacy, hope, resiliency and optimism have 70% influences on the dependent variable. Meanwhile, the other 30% may be influenced by other factors. On the other hand, according to the result of multiple regression analysis, all the independent variables have a significant relationship toward job performance in Management Service Unit, Public Service Department (PSD), Putrajaya. Hence, the organization should know the factors that can contribute to the job performance of employees.